Sraffa and Althusser reconsidered neoliberalism advancing in South Africa, England, and Greece - Zarembka, Paul (Emerald, 2014)
This volume examines the recent advance of neoliberalism. The volume begins with a very extensive study of the archives of Piero Sraffa, which suggests the importance of Marx's influence on his work. The following chapters address the recent multifaceted advance of neoliberalism, with a focus on three current instances. Firstly, suggesting uneven development as in Rosa Luxemburg. South African multi-billion dollar investments in two fossil-fuel projects have recently cemented debtor relations to the World Bank and the Chinese Development Bank, while generating activist opposition in this era of climate crisis. A second instance focuses on secondary school teachers in England whose work load is not only increasing but also increasingly commodified and judged, a development that represents the penetration of abstract labor and alienation, as in Marx. The third example examines the credit bubbles in Greece, noting them as an example of the progency of fictitious capital. The remaining chapters include a critique of Althussers interpretation of the Marxist philosophy of science, and a continued discussion regarding the concept of a labor aristocracy, engaging the work of Zak Cope.
Keywords: Sraffa, Piero.; Althusser, Louis, -- 1918-1990.; Neoliberalism -- South Africa.; Neoliberalism -- England.; Neoliberalism -- Greece.; Marxian economics.; elektronické knihy; electronic books